Urban high-rise public housing for squatter resettlement: Desa Mentari as a case study - Abdul Aziz, Faziawati; Ujang, Norsidah; Abu Bakar, Nor Azlina (Jomard Publishing, 2022)
Squatter settlements have long been negatively stigmatised in Malaysia, where their image is politically and morally unacceptable against an urban backdrop. In the 1980s, 90s and the early Noughts, Kuala Lumpur sent through rapid industrialisation and urbanisation, resulting in the extensive demolition of squatter settlements for new mega-developments. With the launching of the Zero Squatters 2005 program, former squatter dwellers were relocated into low-cost high-rise public housing, with no concerns about the impacts. This paper will discuss the characteristics of these public housing for former squatter dwellers. Due to its characteristics as low-cost high-rise residential complexes for relocated former squatter dwellers, Desa Mentari was selected as a case study. The data was analysed against the five domains of the Infrastructure of Everyday Life: home and neighbourhood, enjoyment, sources of support, having a say and making ends meet. It was found that the development of Desa Mentari only meets the minimum requirements, bad design, a poor physical environment and inadequate facilities and services, which lead to frustrations and ultimately contribute to other social problems in the neighbourhood. The work conclusively argues that planning and housing policy should be informed by the daily life needs and activities of specific groups within society.